Clinical uveitis evaluation and its value in the diagnosis of spondyloarthritis - Alla Aleksandrovna Godzenko; I Yu Razumova; A G Bochkova (Научно-практическая ревматология)
Objective: to estimate the value of clinical parameters of uveitis for the diagnosis of spondyloarthritis (SA). Subjects and methods. One hundred and five uveitis patients referred by ophthalmologists to the Research Institute of Rheumatology, Russian Academy of Medical Sciences, in 2007–2009 were examined. X-ray study of the pelvis and lumbar spine, HLA-B27 test, and objective examination were performed in all the patients to detect inflammatory back pain, arthritis, and enthesitis. Results. The diagnosis of SA was verified in 60 patients: 24 had ankylosing spondylitis, 2 had reactive arthritis, and 38 had undifferentiat ed SA. The diagnosis of SA was discarded in 45 patients. Subsequent examination of these patients diagnosed BehНet's disease in 2 of them, sarcoidosis in 1, toxoplasmosis in 4, virus infection-associated uveitis in 8, Fuchs' syndrome in 1, and unspecified uveitis in 29. There was unilateral uveitis in 51 (85%) of the 60 patients with SP and in 26 (58%) of the 45 patients without SP (p = 0.0033); alternat ing eye lesion in 30 (50%) of the 60 patients with SP and in 4 (8.9%) of the 45 patients without SP (p = 0.00001); anterior uveitis in 57 (95%) of the 60 patients with SP and in 32 of the 45 patients without SP (p = 0.0017); posterior uveitis in 6 (10%) of the 60 patients with SP and in 20 (44%) of the 45 patients without SP (p = 0.0001); panuveitis in 2 (3.3%) of the 60 patients with SP and in 10 (22.2%) of the 45 patients without SP (p = 0.0039), acute recurrent uveitis in 15 (33.3%) of the 45 patients without SP and in 44 (73%) of the 60 patients with SP (p = 0.0001). The age at onset was less than 30 years in 38 patients with SP and in 19 patients without SP (p = 0.04). Conclusion. The estimation of the location and course of uveitis is important in diagnosing SP that is probable in patients with acute anteri or unilateral uveitis with alternating eye lesion, which occurred before the age of 30 years.